2001
DOI: 10.1074/jbc.m100142200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Modification and Inactivation of the Proteasome during Coronary Occlusion/Reperfusion

Abstract: Restoration of blood flow to ischemic myocardial tissue results in an increase in the production of oxygen radicals. Highly reactive, free radical species have the potential to damage cellular components. Clearly, maintenance of cellular viability is dependent, in part, on the removal of altered protein. The proteasome is a major intracellular proteolytic system which degrades oxidized and ubiquitinated forms of protein. Utilizing an in vivo rat model, we demonstrate that coronary occlusion/ reperfusion result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
257
0
4

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 334 publications
(276 citation statements)
references
References 49 publications
15
257
0
4
Order By: Relevance
“…Oxidative stress-induced modifications in proteins have been documented in different cell types [21,22,38]. Consistent with this observation, our results demonstrate that increased protein carbonylation seen in T lymphocytes from elderly donors could be mimicked in T cells from young donors following exposure to pro-oxidant.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Oxidative stress-induced modifications in proteins have been documented in different cell types [21,22,38]. Consistent with this observation, our results demonstrate that increased protein carbonylation seen in T lymphocytes from elderly donors could be mimicked in T cells from young donors following exposure to pro-oxidant.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this observation, our results demonstrate that increased protein carbonylation seen in T lymphocytes from elderly donors could be mimicked in T cells from young donors following exposure to pro-oxidant. As the proteasome is largely implicated in the removal of oxidized proteins [18][19][20][21][22]39], accumulation of carbonylated proteins during aging and following pro-oxidant exposure suggests that proteasome may itself be a target of oxidative stress. Indeed, cross-linked proteins formed by prolonged oxidation and/or HNE modifications have previously been shown to inhibit the proteasome [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the three catalytic sites can be differentially affected in aged tissues, suggesting different mechanisms of inhibition. Exclusive inhibition of the chymotrypsin-like (Bulteau et al, 2000;Keller et al, 2000;Louie et al, 2002;Ponnapan et al, 1999), caspase-like (Anselmi et al, 1998;Conconi and Friguet, 1997) and trypsin-like (Hayashi and Goto, 1998;Radak et al, 2002) activities has been reported. Taken together, the tissuespecific differences in how aging affects proteasome function suggests exposure to environmental stressors (i.e., light, free radicals), protective mechanisms (i.e., heat shock proteins, antioxidants), or differences in proteasome subtypes (i.e., constitutive versus immunoproteasome) that are unique to each cell type can influence the extent and specificity of the effect.…”
Section: Discussion Altered Proteasome Function With Agingmentioning
confidence: 99%
“…Moreover, treatment of kidney with ferryl nitriloacetate and brain ischemia-reperfusion were associated with decreased proteasome function and modification of the proteasome by the lipid peroxidation product 4-hydroxy-2-nonenal [56,57]. Specific modification of three proteasome subunits by 4-hydroxy-2-nonenal was also associated with inactivation of the trypsin-like activity upon cardiac ischemia-reperfusion [58]. In addition, we have recently found that in vitro treatment of proteasome purified from rat heart results in the preferential inactivation of the trypsin-like activity and the modification of restricted set of proteasome subunits that include those previously reported to be targeted upon ischemia-reperfusion, hence making 4-hydroxy-2-nonenal modification of proteasome as a likely mechanism for proteasome inactivation in vivo [59].…”
Section: Protein Maintenance and Protection Against Oxidative Stressmentioning
confidence: 97%